SUPPORTING VOCABULARY LEARNING IN DEAF LEARNERS THROUGH ASSISTIVE TECHNOLOGY: A STUDY OF THE POCKET SIGN APP - Wiwin Suriani; Salasiah Ammade; Siti Hajar Larekeng (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Teaching the English language to deaf students presents both unique challenges and tremendous opportunities for the teacher. Teachers of deaf learners are required to use certain strategies in instruction. The study focused on determining the extent to which the Pocket Sign app, as an assistive technology, supports vocabulary development among deaf students. The study employed a quantitative method with a one-group pre-test post-test design. The instrument of the study was a vocabulary test, which was analysed quantitatively using a paired sample t-test. The study involved six deaf students of SLBN Lutang in grades 4, 5, and 6. The study found that there was a significant difference between the students’ pre-test and post-test, which means that the H0 was rejected and the H1 was accepted. The study concludes that the use of the pocket sign app as an assistive technology supports the vocabulary learning of the deaf learners.